A Brief History of Medieval Monasticism in Denmark (with Schleswig, Rügen and Estonia) - Gøgsig Jakobsen, Johnny Grandjean (Religions, 2021)
Monasticism was introduced to Denmark in the 11th century. Throughout the following five centuries, around 140 monastic houses (depending on how to count them) were established within the Kingdom of Denmark, the Duchy of Schleswig, the Principality of Rügen and the Duchy of Estonia. These houses represented twelve different monastic orders. While some houses were only short lived and others abandoned more or less voluntarily after some generations, the bulk of monastic institutions within Denmark and its related provinces was dissolved as part of the Lutheran Reformation from 1525 to 1537. This chapter provides an introduction to medieval monasticism in Denmark, Schleswig, Rügen and Estonia through presentations of each of the involved orders and their history within the Danish realm. In addition, two subchapters focus on the early introduction of monasticism to the region as well as on the dissolution at the time of the Reformation. Along with the historical presentations themselves, the main and most recent scholarly works on the individual orders and matters are listed.